2022
DOI: 10.1155/2022/6563193
|View full text |Cite|
|
Sign up to set email alerts
|

Observation of Clinical Efficacy of Anisodamine and Chlorpromazine in the Treatment of Intractable Hiccup after Stroke

Abstract: Objective. This study is aimed at investigating the clinical efficacy of anisodamine combined with chlorpromazine on intractable hiccups after stroke. Methods. 150 patients admitted to Affiliated Hospital of the Hebei University of Engineering from 2017 to 2021 were selected as the research objects, all of which received the computed tomography (CT) examination. During CT examination, intelligent algorithms were used to segment the images. An unsupervised multilayer image threshold segmentation algorithm was p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 34 publications
0
6
0
Order By: Relevance
“…Some scholars believe that the reflex arc of the hiccup is as follows: The afferent pathway of hiccups includes the sensory fibers of the vagal nerve, the phrenic nerve, and sympathetic nerves from Th6 to Th12; [12,13] ; The hiccup centers mainly include the medulla oblongata, the periaqueductal gray, subthalamic nuclei, phrenic nerve nuclei, reticular formation, and C3 to 5 cervical cord; [12][13][14] the hypothalamus and temporal lobe may have a greater influence on the arc; and; The efferent pathway of hiccups includes the phrenic nerves to the diaphragm, the external intercostal nerves (Th1-Th11) to the intercostal muscles, the cervical spinal nerves to the anterior scalene muscles, and the recurrent laryngeal portion of the vagal nerve to the glottis, which causes glottal closure. [12,14] Many diseases, such as stroke, [15,16] cancer, [17] surgery, [18,19] and COVID-19, [20] can cause hiccup, which can be divided into the following 4 categories according to the etiologies: central, peripheral, global and medication-derived causes. [21] The incidence rate of hiccups in ordinary inpatients is 0.054%, [22] in cancer patients is 3.9% to 4.5%, [23] and in stroke patients is approximately 0.3% (16 per 5309).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Some scholars believe that the reflex arc of the hiccup is as follows: The afferent pathway of hiccups includes the sensory fibers of the vagal nerve, the phrenic nerve, and sympathetic nerves from Th6 to Th12; [12,13] ; The hiccup centers mainly include the medulla oblongata, the periaqueductal gray, subthalamic nuclei, phrenic nerve nuclei, reticular formation, and C3 to 5 cervical cord; [12][13][14] the hypothalamus and temporal lobe may have a greater influence on the arc; and; The efferent pathway of hiccups includes the phrenic nerves to the diaphragm, the external intercostal nerves (Th1-Th11) to the intercostal muscles, the cervical spinal nerves to the anterior scalene muscles, and the recurrent laryngeal portion of the vagal nerve to the glottis, which causes glottal closure. [12,14] Many diseases, such as stroke, [15,16] cancer, [17] surgery, [18,19] and COVID-19, [20] can cause hiccup, which can be divided into the following 4 categories according to the etiologies: central, peripheral, global and medication-derived causes. [21] The incidence rate of hiccups in ordinary inpatients is 0.054%, [22] in cancer patients is 3.9% to 4.5%, [23] and in stroke patients is approximately 0.3% (16 per 5309).…”
Section: Discussionmentioning
confidence: 99%
“…Many diseases, such as stroke, [15,16] cancer, [17] surgery, [18,19] and COVID-19, [20] can cause hiccup, which can be divided into the following 4 categories according to the etiologies: central, peripheral, global and medication-derived causes. [21] The incidence rate of hiccups in ordinary inpatients is 0.054%, [22] in cancer patients is 3.9% to 4.5%, [23] and in stroke patients is approximately 0.3% (16 per 5309).…”
Section: Discussionmentioning
confidence: 99%
“…[82] In addition, Wang et al conducted a study demonstrating that the administration of anisodamine via acupoint injection can treat intractable hiccups following a stroke, and iacupoint injection of anisodamine combined with chlorpromazine produces superior outcomes for patients with intractable hiccups after stroke, while also exhibiting a high level of safety and potential for clinical application. [83] Numerous studies have demonstrated that the co-administration of anisodamine with conventional drug therapy yields enhanced therapeutic outcomes. For instance, the concurrent use of anisodamine and azithromycin has been shown to effectively alleviate childhood mycoplasma pneumonia disease.…”
Section: Other Clinical Applicationsmentioning
confidence: 99%
“…In addition, Wang et al. conducted a study demonstrating that the administration of anisodamine via acupoint injection can treat intractable hiccups following a stroke, and iacupoint injection of anisodamine combined with chlorpromazine produces superior outcomes for patients with intractable hiccups after stroke, while also exhibiting a high level of safety and potential for clinical application [83] …”
Section: Clinical Applicationmentioning
confidence: 99%
“…This article has been retracted by Hindawi following an investigation undertaken by the publisher [ 1 ]. This investigation has uncovered evidence of one or more of the following indicators of systematic manipulation of the publication process: Discrepancies in scope Discrepancies in the description of the research reported Discrepancies between the availability of data and the research described Inappropriate citations Incoherent, meaningless and/or irrelevant content included in the article Manipulated or compromised peer review …”
mentioning
confidence: 99%